In vitro Allelopathic Potential of Leaf Water Extracts of Plantago lanceolata and P. major on the Germination of Some Crops - Onur Yaraş; Nadim Yılmazer (Journal of Advanced Research in Natural and Applied Sciences)
Alongside increasing productivity in plant production, reducing crop losses has become a major focus for the struggle of today’s man against hunger. Allelopathy, an ecological phenomenon in which organisms interfere with each other, can be a useful strategy in agricultural systems, especially for weed management. In this study, the allelopathic effects of leaf water extracts from two weed species, Plantago lanceolata and P. major, on the seed germination of some crop plants, including wheat, sunflower, lentil, bean, carrot, radish, and purslane were investigated. In vitro germination assays were conducted to determine the effects of different dilutions of the stock extract on the germination rate. The results of the study showed that as the concentration of the extracts from both weeds increased, germination rates decreased in all crop plants. As to the seeds that were exposed to P. lanceolata extract, the ones with the most inhibited germination were carrot (11.84-100%), purslane (18.53-100%), radish (6.17-98.84%), lentil (13.77-95.56%), sunflower (17.57-94.98%), and wheat (30.12-78.31%). The seeds of beans (28.69-39.15%), on the other hand, were the least affected. Similarly, for seeds exposed to P. major extract, the ones with the most inhibited germination were carrot (4.67-100%), lentil (65.46-99.55%), purslane (25.09-99.24%), radish (48.69-95.51%), sunflower (43.68-93.16%), and beans (20.70-66.80%), while wheat (12.35-60.62%) seeds were the least affected. If purslane and radish are considered as weeds, our findings suggest that higher concentrations of P. lanceolata and P. major extracts can be effective bioherbicides for controlling these weeds.